Cesarean sections in Brazil's teaching hospitals: an analysis using Robson Classification - Yluska Myrna Meneses Brandão e Mendes; Daphne Rattner (Pan American Health Organization, 2021)
Objective. To determine the distribution of cesarean sections performed in teaching hospitals participating in the Project for Improvement and Innovation in the Care and Teaching of Obstetrics and Neonatology (Apice ON) using the Robson Classification. Methods. Cross-sectional descriptive study on cesarean sections performed at Apice ON hospitals according to the Robson Classification, using secondary data from the 2017 Live Births Information System on the year prior to project implementation, hence a baseline study. Hospitals are described according to their geographic distribution and cesarean section rates, using absolute and relative frequencies. Results. The proportions of newborns by Robson groups were similar to those proposed by the World Health Organization, except for Group 5 (with previous cesarean section) and Group 10 (preterm), with regional differences. The teaching hospitals' average cesarean section rates ranged from 24.8% to 75.1%, exceeding by far the recommended values, even in Robson groups considered low risk for cesarean section (Groups 1 to 4). Conclusions. Brazilian teaching hospitals displayed cesarean section rates higher than those recommended by the World Health Organization for all groups; a worrisome fact, as by teaching they induce attitudes in future professional practices. These results highlight the importance of a reliable information system. Monitoring and evaluation of cesarean sections using the Robson Classification can be an important tool to guide management and propose actions to reduce rates. Countries with high cesarean section rates might explore this hypothesis in their teaching hospitals in order to define policies for the reduction of their rates.